Collaborative Governance Model in Managing International Borders in Riau Islands Province using Partial Least Squares Method - Adji Suradji Muhammad; Tulus Warsito; Ulung Pribadi; Achmad Nurmandi (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2017)
Despite the large number of border management agencies at  both local and national level, there is no guarantee that borders of  Riau Islands   Province are well protected. Most  illegal fishing, mining and human trafficking are attributable to  the lack of  collaboration among various   border management agencies. It also indicates failure to implement effectively collaborative culture, leadership, team process, structure, and  strategic vision.   This study aims to evaluate the implementation of Collaborative Governance Model in the management of Riau Islands Province borders. The  study used a descriptive verification method,  and collected data using an interview technique, while  partial least squares method was used in analyzing the  data. Results swhowed that the  collaborative team process (CTP), turned out to be the dependent variable, while the other   five principles, , inter alia,  structural, cultural, leadership and strategic vision variables were established as the indepdendentindependent variables that influence CTP.